Hubungan Konsumsi Coklat dengan Perburukan Akne Vulgaris pada Remaja dan Dewasa Muda dengan Akne Vulgaris: Laporan Kasus Berbasis Bukti - Shelly; Rizki Irianti Rakasiwi Ningrum; Wresti Indriatmi (PT Kalbe Farma Tbk., 2023)
Introduction: Acne vulgaris (AV) is a common dermatological problem. AV can occur in all age groups, especially in the adolescent. Chocolate is one of the most consumed foods by teenagers, its relationship with AV has not been established. Objective: To determine whether chocolate consumption is associated with worsening AV in adolescents and young adults with AV. Methods: Article searches used the PubMed, EMBASE, Proquest, and Scopus databases using the keywords adolescent and young adult, chocolate, acne. Search for relevant studies was also carried out from the reference list. Results: Three articles met the eligibility criteria. Critical reviews demonstrated that white chocolate is associated with an increase in total, non-inflammatory, and inflammatory acne lesions in adolescents and young adults with AV. There is still no agreement regarding the association of dark chocolate with worsening AV in adolescents and young adults with AV. Conclusion: White chocolate is associated with worsening AV in adolescents and young adults with AV, whereas the relationship of dark chocolate with worsening of AV in adolescents and young adults with AV is still inconclusive.